Clinical profile of persistent pulmonary hypertension in new born: experience in an extramural institution - S., Harish; C. N., Kamalarathnam (International Journal of Contemporary Pediatrics, 2018)
Background: Persistent pulmonary artery hypertension of the new born (PPHN) has an incidence of 1.9 per 1000 live births with a mortality of 12 to 29%. In our tertiary care referral institute, the mortality was relatively high. A department audit was undertaken which will help us to introspect and to reason out the factors favouring survival and mortality in our NICU. Methods: Neonates with the diagnosis of PPHN from January 2016 to December 2016 were identified from our department database. After excluding cardiac causes of pulmonary hypertension, transport, prenatal, perinatal and post-natal data, treatment details and outcome information was collected from case records. The statistical analysis was calculated with SPSS software. Mean, standard deviation was calculated for continuous variables. Chi square test and Fischer’s exact test was used to test the association between categorical variables and t test for continuous variables. Results: The incidence PPHN in our unit was 1.5%. The average duration of hospital stay was 17 days. Among the 45.7 % of babies, PPHN was secondary to MAS, followed by CDH (22.3 %). Based on oxygenation index, 15 babies, 42.3% had mild, 10 babies, 28.6% had moderate, 8 babies, 22.3% had severe PPHN and 3 babies ,8.6% had severe PPHN. Overall mortality was 42.3%. SpO2 on arrival at emergency room, adequacy of cardiorespiratory during transport and presence of shock is significantly associated with mortality. Conclusions: This study show MAS and CDH are common causes of PPHN. Severity of illness at arrival was predictive of high mortality. Prior stabilization and adequate transport may improve outcomes.